PENGGUNAAN MEDIA KONKRET UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA PADA MATERI BANGUN RUANG SISWA KELAS V MIN 4 KOTA BANDA ACEH - Nurul Fazhilah; Diandita, Elly Rizky; Azkia, Nura (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical literacy among elementary school students remains low, particularly in the topic of three-dimensional geometry. Preliminary observations at MIN 4 Banda Aceh revealed that only 37% of students achieved the Minimum Mastery Criterion (MMC) of 76, while 63% failed to meet the standard, with an average score of 68. Therefore, this study aimed to examine the effect of using concrete media on the mathematical literacy skills of fifth-grade students in learning three-dimensional geometry at MIN 4 Banda Aceh. This study employed a quantitative approach using a One-Group Pretest–Posttest Design. The sample consisted of 35 students selected through purposive sampling. Data were collected using a mathematical literacy test and observation sheets, then analyzed using validity, reliability, normality, N-Gain, and Paired Sample t-test analyses. The results showed that the mean pretest score increased from 39.20 to 85.20 on the posttest, with an N-Gain score of 0.75 (high category). The Paired Sample t-test yielded a significance value of 0.000 (< 0.05), indicating that the use of concrete media had a significant positive effect on improving students' mathematical literacy skills.